Development of the Method for Forecasting and Calculating the Operation of Sorption Systems for Purifying the Generator Gas Based on Dolomite Use. Part I - Malko M.V.; Vasilevich S.V.; Mitrofanov A.V.; Mizonov V.E. (Problems of the Regional Energetics, 2021)
A trend towards energy diversification creates the expansion of small energy facilities that in-volve the production of solid fuel generator gas, rather than its direct combustion. The economic indicators of such facilities significantly depend on the efficiency of the generator gas purifica-tion. A promising sorbent for the purification of the generator gas is dolomite. When working as a sorbent, dolomite particles usually form a layer, through which the generator gas that is heating them is filtered. The objective of the study is to determine kinetic parameters of the thermal de-composition of dolomite, depending on the size of the sample. It was achieved using the ther-mogravimetric study of the thermal decomposition of single dolomite particles under static con-ditions at various temperatures. The most significant scientific result was that a dependence of the kinetic parameters of the gross reaction on the size of the initial particle is revealed, and a regression equation was proposed for its quantitative assessment. In addition, since the heat treatment process of the material was fairly long lasting, and the sizes of the particles allowed them to be referred to thermally thin bodies, it was inferred that the effect of a grain size on the reaction kinetics should be explained through the description of the evacuation process of gase-ous reaction products from the material. The significance of the results of the study lies in the fact that a particle size must be considered as a factor that affects the progress of the technologi-cal process, which increases the reliability of the calculation of sorption-catalytic systems based on the use of dolomite.